The structure of forensic characteristics of murders committed by convicts in prisons - K. H. Shelenina (Bulletin of Kharkiv National University of Internal Affairs)
In order to keep and strengthen law and order in prisons it is very important to have both the final results of investigating crimes committed by convicts, and the results of certain procedural actions that ensure the timeliness and validity of criminal proceedings, the rapid establishment of a perpetrator by the help of evidence, to take necessary measures for his isolation from other convicts, the urgency of identifying and eliminating the causes and conditions that contributed to the commission of a crime. Investigation of a crime in accordance with the above mentioned requirements allows completely, comprehensively and objectively to establish the circumstances, which are subject to proving within criminal proceedings. Preliminary clarification of such circumstances is a necessary precondition for proper hearing the case by the court and the appointment of legal and substantiated criminal penalties for guilty party. This allows to achieve the objectives of general and special crime prevention by persons held in prisons in the most effective method.